Persistent Hiccup in Supratentorial Infarction with Global Aphasia: A Case Report - Putu, Utamia Suma Masyuni; Vincent Ongko Wijaya; Ni Ketut Ayu Sudiariani (Acta Neurologica Indonesia, 2026)
ABSTRACTIntroductionA persistent hiccup is an involuntary contraction involving the diaphragm and intercostal muscle that lasts more than 2 days until a month. This condition is often associated with cerebrovascular infarction in the brainstem region. In contrast, persistent hiccup related to ischemic stroke in the supratentorial region was rarely reported. Here, we describe a patient with a persistent hiccup accompanied by global aphasia in acute supratentorial infarction. Case Summary A male, 61 years old Balinese, right-handed, was admitted due to palpitation. In the emergency room, the patient developed sudden right-sided weakness and an inability to speak. Neurological examination showed right-sided hemiplegia with muscle strength of 1 and global aphasia. EKG showed Rapid Atrial Fibrillation. Non-Contrast CT-Scan showed acute cerebral infarction within the left middle cerebral artery territory. Afterward, the patient experienced hiccups from the time he was in the emergency unit until he was discharged, and the hiccups lasted for more than 7 days. The patient was treated with anticoagulant and neuroprotectant alongside supportive therapy. The hiccup was treated with oral chlorpromazine. Discussion The central hiccup component is believed to lie in the medulla oblongata. Although the exact mechanism of persistent hiccups is still unclear, global aphasia, which involves a large part of the dominant hemisphere, may provide a new insight into the pathophysiology of hiccups. Conclusion Persistent hiccups may occur in supratentorial lesions with global aphasia, where a large portion of the dominant hemisphere is affected.